(untitled) (IJM: Journal of Multidisiplinary, 2025)
The aim of this research is to find out how much influence operational income and operational costs have on net profit in property and real estate companies listed on the Indonesia Stock Exchange for the 2020-2023 period. The verification method with a quantitative approach is the method used in this research which is sourced from profit and loss reports of property and real estate companies. Purposive sampling was used to take samples so that 56 profit and loss reports were taken from 14 companies for the 2020-2023 period. To simplify the analysis process, multiple linear analysis was used in this research. The research results show that operational income (X1) has a partial effect on net profit where the t table value is (7.111 > 2.00488) and the significance value is (0.001 < 0.05). Operational costs (X2) partially have no effect on net profit as evidenced by the t table value (-1.625 < 2.00488) and significance (0.212 > 0.05). And the two X variables simultaneously influence net profit where the calculated F value is greater than the table F value (134.397 > 3.17). And the significance value is 0.001 which means it is smaller than 0.05 (0.001 < 0.05).